Different pathogenicities of Rice stripe virus from the insect vector and from viruliferous plants. Issue 1 (20th November 2015) - Zhao, Wan; Yang, Pengcheng; Kang, Le; Cui, Feng
Summary: Persistent plant viruses usually depend on insects for their transmission; they cannot be transmitted between plants or through mechanical inoculation. However, the mechanism by which persistent viruses become pathogenic in insect vectors remains unknown. In this study, we used Rice stripe virus (RSV), its insect vector Laodelphax striatellus and host plant ( Oryza sativa ) to explore how persistent viruses acquire pathogenicity from insect vectors. RSV acquired phytopathogenicity in both the alimentary tract and the salivary gland of L. striatellus . We mechanically inoculated RSV into rice O. sativa leaves through midrib microinjection. Insect‐derived RSV induced a typical stripe symptom, whereas plant‐derived RSV only produced chlorosis in rice leaves. Insect‐derived RSV had higher expression of genes rdrp, ns2, nsvc2, sp and nsvc4 than plant‐derived RSV, and the latter had higher expression of genes cp and ns3 than the former in rice leaves. Different from plant‐derived RSV, insect‐derived RSV damaged grana stacks within the chloroplast and inhibited photosynthesis by suppressing the photosystem II subunit psbp . This study not only presented a convenient method to mechanically inoculate RSV into plants, but also provided insights into the different pathogenic mechanisms of RSV from the insect vector and from viruliferous plants.